The impact of national policies on accessibility to quality early childhood care and education in Malaysia: Policymakers’ perspectives - Yoke-Yean, Lydia Foong; Soo-Boon, Ng; Poai-Hong, Wong; Hui-Shen, Carynne Loh; Mohd Multazam Khair, Nurul Salwana; Haq, Faridah Serajul; Dhamotharan, Mogana; Che Mustafa, Mazlina (Southeast Asia Early Childhood Journal, 2021)
All children have the right to a safe and nurturing environment that promotes their holistic development. Accessibility is an important gateway to inclusive education where all children including disadvantaged children such as indigenous children, special needs children and children at risk are given equal access to quality early childhood care and education (ECCE). In ensuring inclusive accessibility to ECCE, many countries including Malaysia have instituted policies in relation to the provision of childcare and preschool education. These policies are expected to make a significant difference to the way practitioners work to achieve the best outcomes. This paper reports on a research study to examine the impact of the existing policies on the accessibility to quality ECCE in Malaysia. As part of a larger research project, this study employs a qualitative methodology that used a purposive sampling method. 54 participants were involved consisting government official and leaders of non-government agencies related to ECCE in Malaysia. A team of researchers conducted individual interviews and focus group interviews for the participants who consented to the research. Data collected were transcribed verbatim and analyzed using inductive thematic analysis method involving three cycles of rigorous analytic coding and review processes. The findings of this study indicated the participants are aware of the accessibility related policies they are directly dealing with, and the major themes expressed were inter-agency cooperation to achieve enrolment target; questioning the status quo of the existing procedures; and challenges in providing support services for children with special needs; and inclusion of children with disabilities. The challenges to accessibility are mostly related to disadvantaged children and weakness in the governance and gaps of implementation. Policy reviews need to be systematized into programme planning to ensure high quality ECCE services are accessible to all children in Malaysia.